1987
DOI: 10.1002/polb.1987.090250607
|View full text |Cite
|
Sign up to set email alerts
|

Structure‐permeability relationships in silicone polymers

Abstract: SynopsisPermeability coefficients P for He, and C3H, in 12 different silicone polymer membranes were determined at 35.0"C and pressures up to 9 atm. Values of F for CO,, CH,, and C,H, were also determined a t 10.0 and 55.0"C. In addition, mean diffusion coefficients D and solubility coefficients S were obtained for CO,, CH,, and C3H, in 6 silicone polymers a t 10.0, 35.0, and 55.0"C. Substitution of increasingly bulkier functional groups in the side and backbone chains of silicone polymers results in a signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
225
2
4

Year Published

1997
1997
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 432 publications
(252 citation statements)
references
References 14 publications
21
225
2
4
Order By: Relevance
“…NOA 81 was cured through the PDMS stamp by exposure to UV-light for 2 min (8 W at 365 nm). The curing through the PDMS stamp leaves a thin layer of NOA 81 at the NOA 81/PDMS interface uncured [37,134,135] and therefore allows for sealing the device with a second layer of Kapton foil with no need for an additional glue or adhesive. After curing of the NOA 81, the PDMS stamp was carefully removed leaving the cured NOA 81 film on the Kapton foil (see Fig.…”
Section: Kapton-noa 81mentioning
confidence: 99%
“…NOA 81 was cured through the PDMS stamp by exposure to UV-light for 2 min (8 W at 365 nm). The curing through the PDMS stamp leaves a thin layer of NOA 81 at the NOA 81/PDMS interface uncured [37,134,135] and therefore allows for sealing the device with a second layer of Kapton foil with no need for an additional glue or adhesive. After curing of the NOA 81, the PDMS stamp was carefully removed leaving the cured NOA 81 film on the Kapton foil (see Fig.…”
Section: Kapton-noa 81mentioning
confidence: 99%
“…Its low glass transition temperature (−129 • C) results in extremely high permeation through the membrane for a wide range of gases due to the flexible polymer backbone. However, it is limited in mechanical strength and selectivity particularly for highly condensable hydrocarbons in admixture with permanent gases [4][5][6]. For example, our previous work [7,8] showed that PDMS coated membrane can be plasticized by propane and propylene, resulting in significant permeance increases for both hydrocarbons and nitrogen in a quaternary mixture of propane, propylene, ethylene and nitrogen, therefore, the selectivities of hydrocarbons to nitrogen were not as high as expected.…”
Section: Introductionmentioning
confidence: 99%
“…Recently Gomes et al [18] reported the correlation of gas permselectivities with the contents of PDMS/poly(tetramethylene glycol) soft segments for the thin film membranes made from polyurethane dispersions (PUDs). It is interesting to note that n-C 4 H 10 /CH 4 selectivity for the gas mixture was higher than the ratio of individual gas permeabilities, indicating a possibility of application of this PUD material for n-C 4 H 10 /CH 4 separation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, nanoscale molecular sievesare more suitable for commercialization of nanocomposite membranes whereas they have very thin selective layers than micron-sized zeolites ormolecular sieves. Finally, the possibility of additional functionalization and surface coating of membrane that can further enhance sorption effects in these particles and raise gas selectivity, have been investigated [19][20][21]. As a new work, the functionalization of particles was performed by DMDCS.…”
Section: Introductionmentioning
confidence: 99%